Enacting policy: the capacity of school leaders to support early career teachers through policy work - Sullivan, A.; Morrison, Chad (Australian Association for Research in Education, 2014)
© 2014, The Australian Association for Research in Education, Inc. Early career teachers often feel overwhelmed by the complex, intense and unpredictable nature of their work. Recently, policy initiatives have been introduced to provide new teachers with extra release-time from face-to-face classroom teaching duties to assist them in their transition to the workforce. This paper reports on a critical policy study that investigated the enactment of this policy initiative. A data set was created from a larger qualitative study which investigated early career teacher resilience. Drawing on a policy enactment theoretical ‘toolbox’, the findings indicate that school leaders can empower early career teachers to move beyond being ‘receivers’ of policy to assume a more active policy role. This paper argues that school leaders are very powerful in their capacity to enact policy to ensure strategic access to appropriate on-going learning opportunities to support early career teachers.